2020
DOI: 10.1111/fog.12466
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and movement patterns of blackbelly rosefish in the NE Atlantic Ocean (Azores archipelago)

Abstract: Blackbelly rosefish Helicolenus dactylopterus (Delaroche, 1809) is one of the most important species of the demersal/deep‐water assemblages fished in the NE Atlantic Ocean (Azores archipelago). However, there is insufficient information about the stock structure of this species to support analytical resource assessments and it is currently managed with a precautionary approach. Here, we examine the depth and temporal distribution, size composition, sex, and movement patterns of blackbelly rosefish in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
3
15
0
1
Order By: Relevance
“…However, the applicability of this hypothesis to the NE Atlantic needs to be investigated. Similar depth-size trends have been reported for other demersal and deep-water fish species, such as the blackbelly rosefish Helicolenus dactylopterus [53], Kaup's arrowtooth eel Synaphobranchus kaupi [54], and the greater forkbeard Phycis blennoides [55]. Although the larger-deeper distribution pattern is a common tendency in deep-sea fish assemblages, it cannot be considered a general rule [56,57].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the applicability of this hypothesis to the NE Atlantic needs to be investigated. Similar depth-size trends have been reported for other demersal and deep-water fish species, such as the blackbelly rosefish Helicolenus dactylopterus [53], Kaup's arrowtooth eel Synaphobranchus kaupi [54], and the greater forkbeard Phycis blennoides [55]. Although the larger-deeper distribution pattern is a common tendency in deep-sea fish assemblages, it cannot be considered a general rule [56,57].…”
Section: Discussionsupporting
confidence: 65%
“…In this sense, additional contributions have been provided through empirical estimations of relevant biological and fishery parameters, such as length at first maturity (L m ), length at maximum possible yield (L opt ), life span (t max ), and theoretical age at length zero (t 0 ), using the estimated growth parameters (L ∞ and k; Table 2) [65,66]. Like other deep-water species [18,53,[67][68][69][70], M. moro can be considered vulnerable to overfishing because of its large size, slow growth, low natural mortality (Table 2), long life span, and late maturity (Table S1). However, besides the observed low E and F (Table 2), the empirical equations suggested an apparently healthy fished population in the Azores, with the length at which 100% of individuals are vulnerable to capture (L c ; Table 2) above the L m and L opt (Table S1), and the mean L F in the catch (Figure 5) above the L c , L m , and L opt .…”
Section: Discussionmentioning
confidence: 99%
“…Fishery‐dependent data also showed a decreasing trend in CPUE indices over the years in both seamount groups for all species. For species such as H. dactylopterus and P. phycis, which have distribution by metapopulations and high bottom dependence (Santos et al., 2020c; Santos, Silva, et al, 2019), this trend became evident also in survey‐derived abundance indices (Figure 4) and this may be the result of a greater vulnerability of these species to the fishing effects. This scenario becomes more worrying in the eastern banks, where coupled with the decreasing trend in the CPUE index, there is an increase in fishing effort (decreases CPUE index, increases effort, increases landings; Figures 7‐8) and reduction in species lengths when compared to central banks (Açores and Princesa Alice; Figures 5–6).…”
Section: Discussionmentioning
confidence: 93%
“…Despite this broad applicability, the low tag‐recapture rate observed in the present study (1% of total tags) limited the ability to perform additional quantitative analyses on population dynamics. Recently, Santos et al (2020c) identified the same difficulty when analysing Helicolenus dactylopterus Delaroche tagging data. Although the effect of fish death due to the tagging process was considered constant, other factors, such as unreported tags by fishers, may reduce tag recovery rate (Santos et al 2020c).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Santos et al (2020c) identified the same difficulty when analysing Helicolenus dactylopterus Delaroche tagging data. Although the effect of fish death due to the tagging process was considered constant, other factors, such as unreported tags by fishers, may reduce tag recovery rate (Santos et al 2020c).…”
Section: Discussionmentioning
confidence: 90%